The Deoxyhypusine Synthase Mutant dys1-1 Reveals the Association of eIF5A and Asc1 with Cell Wall Integrity - Galvão, Fabio Carrilho [UNESP]; Rossi, Danuza [UNESP]; Silveira, Wagner da Silva [UNESP]; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei Fernando [UNESP] (Public Library of Science (PLoS), 2013)
The putative eukaryotic translation initiation factor 5A (eIF5A) is a highly conserved protein among archaea and eukaryotes that has recently been implicated in the elongation step of translation. eIF5A undergoes an essential and conserved posttranslational modification at a specific lysine to generate the residue hypusine. The enzymes deoxyhypusine synthase (Dys1) and deoxyhypusine hydroxylase (Lia1) catalyze this two-step modification process. Although several Saccharomyces cerevisiae eIF5A mutants have importantly contributed to the study of eIF5A function, no conditional mutant of Dys1 has been described so far. In this study, we generated and characterized the dys1-1 mutant, which showed a strong depletion of mutated Dys1 protein, resulting in more than 2-fold decrease in hypusine levels relative to the wild type. The dys1-1 mutant demonstrated a defect in total protein synthesis, a defect in polysome profile indicative of a translation elongation defect and a reduced association of eIF5A with polysomes. The growth phenotype of dys1-1 mutant is severe, growing only in the presence of 1 M sorbitol, an osmotic stabilizer. Although this phenotype is characteristic of Pkc1 cell wall integrity mutants, the sorbitol requirement from dys1-1 is not associated with cell lysis. We observed that the dys1-1 genetically interacts with the sole yeast protein kinase C (Pkc1) and Asc1, a component of the 40S ribosomal subunit. The dys1-1 mutant was synthetically lethal in combination with asc1Δ and overexpression of TIF51A (eIF5A) or DYS1 is toxic for an asc1Δ strain. Moreover, eIF5A is more associated with translating ribosomes in the absence of Asc1 in the cell. Finally, analysis of the sensitivity to cell wall-perturbing compounds revealed a more similar behavior of the dys1-1 and asc1Δ mutants in comparison with the pkc1Δ mutant. These data suggest a correlated role for eIF5A and Asc1 in coordinating the translational control of a subset of mRNAs associated with cell integrity. © 2013 Galvão et al.
Keywords: deoxyhypusine synthase; deoxyhypusine synthase 1; deoxyhypusine synthase 1 1; fungal protein; hypusine; initiation factor 5A; protein Asc1; protein kinase C; sorbitol; unclassified drug; allele; asc1 gene; binding affinity; cell growth; cell wall; cell wall integrity; controlled study; cytolysis; deoxyhypusine synthase 1 gene; eukaryotic translation initiation factor 5A gene; gene; gene function; gene interaction; gene overexpression; genetic identification; mutant; nonhuman; osmosis; polysome; protein depletion; protein function; protein kinase C gene; protein modification; protein protein interaction; protein synthesis; ribosome; RNA translation; sensitivity analysis; translation regulation; wild type; yeast